Challenges to European Welfare Systems
IX, 863 p. 175 illus., 2 illus. in color.
Keywords: This book provides the first comprehensive analyses of the challenges all European welfare systems have been facing since 2007, combining in-depth country-based studies and comparative chapters. It focuses on: 1) the economic and financial crisis, 2) demographic change, and 3) the balance between avoiding risks and opening up opportunities in social policy. The results show that European welfare systems tend to face the same challenges in different ways and that also their responses to those challenges differ considerably. Although the EU also plays a part in shaping national welfare systems, it becomes evident that European welfare systems are by no means converging: in terms of social policy, national diversity within Europe is still a major factor that will shape future developments in European welfare systems.